2021
DOI: 10.1371/journal.pone.0246422
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically polymerised polyphenols prepared from various precursors potentiate antigen-specific immune responses in both mucosal and systemic compartments in mice

Abstract: Despite significant modern medicine progress, having an infectious disease is a major risk factor for humans. Mucosal vaccination is now widely considered as the most promising strategy to defeat infectious diseases; however, only live-attenuated and inactivated mucosal vaccines are used in the clinical field. To date, no subunit mucosal vaccine was approved mainly because of the lack of safe and effective methodologies to either activate or initiate host mucosal immune responses. We have recently elucidated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Subsequently, the obtained samples were incubated for 1 h at 4 • C, and the serum samples were collected after centrifugation at 1200× g for 30 min. To monitor the induction of OVA-specific IgA in nasal washes, nasal wash samples (250 µL of cold PBS) were collected [18,19]. The samples were stored at -80 • C until further analysis.…”
Section: Immunization Schedule and Blocking Effect Of Anti-il-6r Anti...mentioning
confidence: 99%
“…Subsequently, the obtained samples were incubated for 1 h at 4 • C, and the serum samples were collected after centrifugation at 1200× g for 30 min. To monitor the induction of OVA-specific IgA in nasal washes, nasal wash samples (250 µL of cold PBS) were collected [18,19]. The samples were stored at -80 • C until further analysis.…”
Section: Immunization Schedule and Blocking Effect Of Anti-il-6r Anti...mentioning
confidence: 99%
“…In a previous study, we have reported that intranasal administration of pCA with ovalbumin (OVA), as a model antigen, enhanced OVA-specific antibody production in the mucosal and systemic compartments [25,26]. In this study, we aimed to develop a nasal vaccine against pneumococcal infection using pCA.…”
Section: Nasal Immunization Of a Pspa Antigen With Pca Elicits Pspa-specific Antibody Responses In The Mucosal And Systemic Compartmentsmentioning
confidence: 99%
“…This method resulted in the induction of a higher titer of antigen-specific mucosal and systemic antibody responses in mice. Since intranasal administration of pCA does not exert any toxicity in mice, pCA maybe useful to the development of a safe mucosal vaccine system [25,26]. Further, the sources of CA and HRP are coffee beans and horseradish, respectively, which are easily available.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained samples were incubated for 1 h at 4 • C, and serum samples were collected after centrifugation at 1200 × g for 30 min. To monitor the induction of OVA-specific immunoglobulin A (IgA) in nasal washes, nasal wash samples (250 µL of cold PBS) were collected [20][21][22]. The samples were stored at − 80 • C until further analysis.…”
Section: Intranasal Immunization Of Ova Plus Dotap/dc-chol Liposomes ...mentioning
confidence: 99%